Evaluation of anchote (Coccinia abyssinica) genotypes and processing methods for mineral and phytochemical composition - Bogalech Negassa; Amsalu Nebiyu; Weyessa Garedew; Lord Abbey; Raphael Ofoe; Nasir Seyed Mousavi; Bawa Nutsukpo; Tessema Astatkie; Chala G. Kuyu (Journal of Agriculture and Food Research)
Anchote, a vital crop in Ethiopia, is valued for its food, medicinal, social, and economic benefits. Despite it outperforms other root vegetables in yield and nutritional content, its cultivation remains restricted to specific locales, prompting on-farm studies to assess mineral and phytochemical profiles of various anchote genotypes. This research aimed to identify better cooking methods for preserving these essential components. Three genotypes were tested in the on-farm trials across four fields: two local landraces (LV1, LV2) and the Improved Variety Desta 01. A factorial experiment combining three genotypes with two cooking approaches (peeled and unpeeled) was executed to evaluate mineral content (Ca, K, Mg, Na, P, Cu, Mn, Fe, Zn). Results showed significant impacts of cooking methods on potassium (K) and magnesium (Mg) levels (P = 0.01, P = 0.006) and on phenolics and ascorbate content (P = 0.026, P = 0.004). While genotypes did not show significant difference in phytochemical composition, boiling the roots unpeeled proved to be the most effective method for conserving mineral and phytochemical profiles. The study underscores the potential of anchote genotypes as nutrient-rich crops, advocating for their widespread adoption for nutritional and pharmaceutical purposes. Future research avenues should explore anchote's broader biochemical potential for food formulation, processing, and pharmaceutical applications.